Sandwich Generation: Sociological Dynamics In The Traditions Of Madura Society From An Islamic Perspective - Nasith, Ali (FALASIFA : Jurnal Studi Keislaman, 2023)
This research aims to photograph and explore in depth the sociological phenomenon of the sandwich generation in the traditions of the Madurese community in Jember Regency. Especially those related to the sociological construction of the sandwich generation and the motivation for their upbringing from an Islamic perspective. In the process, this research uses a qualitative with ethnographic approach. Data collection techniques were carried out using in-depth interviews and observation. The data analysis used is ethnographic thematic analysis. The research findings in this study are [1] Sandwich generation in the Madurese community tradition is a construction and socio-religious fact, namely a social phenomenon that arises from the community's religious understanding. [2] Parenting motivation in the sandwich generation is driven by moral compensation, affective and theological impulses. Based on these practices and dynamics, Islam provides guidance that devotion to parents in any community and generation must be carried out sincerely and with full respect.